Substrate dependant survivorship of Ecklonia maxima, in southern African kelp communities - West, Adam (Department of Biological Sciences, 2017)
Several south-western Cape Ecklonia maxima communities were examined to determine their basic demography and the effects of substrate selection. Overall percentage substrate composition, stipe lengths and substrate attachment for all kelps were recorded at four sites off the Cape Peninsula. Strength of attachment to different substrates was measured. Selection for substrate type was analysed using Jacobs' index. A substrate of Pyura stolonifera was the most common for juveniles, whereas substrates of rock and conspecific holdfasts were dominant in the larger individuals. No significant difference in strength of attachment was found for kelps less than 50 cm. An analysis of the frequency of single- and multi-stiped holdfasts indicates that survival on rock is greater than on that of holdfasts. Size-class distributions indicate that E. maxima is a shade-tolerant species showing advanced regeneration. Establishment on rock may occur through episodic recruitment escaping grazing pressure. In areas with low grazing intensity, recovery from catastrophic storms may be limited by competition with understorey algae.